1973
DOI: 10.1039/f29736900569
|View full text |Cite
|
Sign up to set email alerts
|

Rotational isomerism and barriers to internal rotation in hydroxyacetonitrile from microwave spectroscopy

Abstract: The microwave spectra of HOCHzCN and DOCHzCN show that the molecule exists as the gauche rotamer in the gas phase. A large number of intense lines converging to a band head near 16 800 MHz for DOCHzCN and 110 700 MHz for HOCHzCN are attributed to the ZI = l+O transitions of the hydroxyl torsion. The rotational constants indicate that cce, the angle between the HOC and OCC planes at the potential minima is approximately 123" from the trans position. Potential functions which reproduce the observed ZI = 140 tors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…5 Examples of alkynes with intramolecular hydrogen bonds investigated by MW spectroscopy include propargyl alcohol (HOCH 2 CCH), 6 3-butyn-2-ol (H 3 CCH(OH)CCH), 7 3-butyn-1-ol (HOCH 2 CH 2 CCH), 8 − 12 4-pentyn-1-ol (HOCH 2 CH 2 CH 2 CCH), 13 propargyl thiol (HSCH 2 C CH), 14 3-butyne-1-thiol (HSCH 2 CH 2 CCH), 15 propargyl s e l e n o l ( H S e C H 2 C  C H ) , 1 6 3 -b u t y n e -1 -s e l e n o l (HSeCH 2 CH 2 CCH), 17 propargyl amine (H 2 NCH 2 C CH), 18 N-methylpropargyl amine (H 3 C(NH)CH 2 CCH), 19 and 1-amino-3-butyne (H 2 NCH 2 CH 2 CCH). 20 Similarly, intramolecular hydrogen bonding has been reported for a number of nitriles comprising hydroxyacetonitrile (HOCH 2 CN), 21 lactonitrile (H 3 CCH(OH)CN), 22 3-hydroxypropanenitrile (HOCH 2 CH 2 CN), 23 3-mercaptopropionitrile (HSCH 2 CH 2 CN), 24 Z-3-mercapto-2-propenenitrile (HSCHCHCN), 25 aminoacetonitrile (H 2 NCH 2 C N), 26,27 3-aminopropionitrile (H 2 NCH 2 CH 2 CN), 28 (Nmethylamino)ethanenitrile (H 3 C−NH−CH 2 CN), 29 2-aminopropionitrile (H 3 C(NH 2 )CHCN), 30 Z-3-amino-2-propenenitrile (H 2 NCHCHCN), 31 and 3-phosphinopropionitrile (H 2 PCH 2 CH 2 CN). 32 In contrast to these many investigations of internal hydrogen bonding with the π-electrons of the triple bonds in alkynes and nitriles, no gas-phase studies of this interaction have been reported for isonitriles (R−NC), the third functional group possessing a triple bond.…”
Section: ■ Introductionmentioning
confidence: 98%
“…5 Examples of alkynes with intramolecular hydrogen bonds investigated by MW spectroscopy include propargyl alcohol (HOCH 2 CCH), 6 3-butyn-2-ol (H 3 CCH(OH)CCH), 7 3-butyn-1-ol (HOCH 2 CH 2 CCH), 8 − 12 4-pentyn-1-ol (HOCH 2 CH 2 CH 2 CCH), 13 propargyl thiol (HSCH 2 C CH), 14 3-butyne-1-thiol (HSCH 2 CH 2 CCH), 15 propargyl s e l e n o l ( H S e C H 2 C  C H ) , 1 6 3 -b u t y n e -1 -s e l e n o l (HSeCH 2 CH 2 CCH), 17 propargyl amine (H 2 NCH 2 C CH), 18 N-methylpropargyl amine (H 3 C(NH)CH 2 CCH), 19 and 1-amino-3-butyne (H 2 NCH 2 CH 2 CCH). 20 Similarly, intramolecular hydrogen bonding has been reported for a number of nitriles comprising hydroxyacetonitrile (HOCH 2 CN), 21 lactonitrile (H 3 CCH(OH)CN), 22 3-hydroxypropanenitrile (HOCH 2 CH 2 CN), 23 3-mercaptopropionitrile (HSCH 2 CH 2 CN), 24 Z-3-mercapto-2-propenenitrile (HSCHCHCN), 25 aminoacetonitrile (H 2 NCH 2 C N), 26,27 3-aminopropionitrile (H 2 NCH 2 CH 2 CN), 28 (Nmethylamino)ethanenitrile (H 3 C−NH−CH 2 CN), 29 2-aminopropionitrile (H 3 C(NH 2 )CHCN), 30 Z-3-amino-2-propenenitrile (H 2 NCHCHCN), 31 and 3-phosphinopropionitrile (H 2 PCH 2 CH 2 CN). 32 In contrast to these many investigations of internal hydrogen bonding with the π-electrons of the triple bonds in alkynes and nitriles, no gas-phase studies of this interaction have been reported for isonitriles (R−NC), the third functional group possessing a triple bond.…”
Section: ■ Introductionmentioning
confidence: 98%
“…3b of Mehringer et al 1993). For the purposes of this study, we assume these same source sizes for warm molecular material and cold molecular material and explicitly calculate Cazzoli et al (1973). the spatial overlap of these regions with the GBT beam as its size varies across the frequency coverage.…”
Section: Observationsmentioning
confidence: 99%
“…Some less perturbed levels were found above 400 GHz, and an assignment and fit was possible by treating the two sublevels separately for K a values up to 2 in the 400-500 GHz range, improving the values of the rotational and the centrifugal distortion constants. The two sublevels were then merged in a unique fit, using the energy difference between the 0 − and 0 + levels determined by Cazzoli et al (1973) as the starting point. We note that this value, 110 700 MHz, is close to the one we determined, 112 672.5526(30) MHz.…”
Section: Analysis Of the Spectramentioning
confidence: 99%
See 2 more Smart Citations